Tasawuf, Kalam Science and Islamic Philosophy - Samuji, Samuji (Jurnal Paradigma, 2023)
Sufism is often distinguished and separated from theology and philosophy in studies of Islamic thought, as if the three had no connection. Whereas in the beginning, tasawwuf was almost inseparable from the science of kalam and Islamic philosophy because the three were united. The relationship between tasawwuf and the science of kalam lies in the discussion of truth. In Sufism, the essence of truth is the disclosure (kasyaf) of the True Truth (Allah) through the eyes of the heart. Sufism finds the truth by passing through several roads or stations. While the truth in the Science of Kalam is in the form of knowing the truth of religious teachings through reasoning, which is then referred to the texts of the Qur'an and Hadith. In the science of kalam, we find discussion of faith and its definition, disbelief and its manifestations, as well as hypocrisy and its limits. Meanwhile, in the science of Sufism, there is discussion of practical paths or methods to feel confidence and peace. While the relationship between the science of Sufism and Islamic philosophy lies in the matter of seeking the essence. Sufism is the search for a spiritual path, unity with absolute truth and mystical knowledge according to paths and sunnah. There are 3 epistemologies in Islamic philosophy, namely bayani epistemology, burhani epistemology and irfani epistemology.